Perancangan Aplikasi Pengenalan Bahasa Jawa Untuk Anak Usia Dini - Wenti Risma Damayanti; Hendra Marcos; Didit Suhartono; Berlilana Berlilana (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2022)
Indonesia is a country that has an area of ​​1.9 million km2 and has many differences, one of which is the difference in language in each region. It is this difference in language that makes a region unique, one of which is the Javanese language which comes from Central Java, East Java, Yogyakarta and its surroundings. The Javanese language itself is a unique language, which has ungguh as a differentiator from other regional languages, therefore efforts are needed to preserve the Javanese language with the main target being early childhood. In this research method using the MDLC (Multimedia Development Life Cycle) method developed by Luther. This method has several stages, including Concept, Design, Material Collecting, Assembly, Testing, and Distribution. Based on the application that the author succeeded in making, it can be concluded that this application is very effective in helping the process of teaching and learning activities in early childhood, and this application has several benefits, namely to preserve Javanese culture, especially in the use of Javanese, making young children use language that is more polite.